Student motivation to learn English using online system during pandemic - Arina Chusnatayaini (Bajang Institute, 2022)
The Indonesian education system is facing new challenges due to the outbreak of the Covid-19 which has shifted the entire learning system in educational institutions to online learning system. This change in the learning system will have an impact on student's learning motivation. Based on these problems, the purpose of this research is to see how students' motivation in learning English with the online learning system at IIK STRADA Indonesia is. This research uses quantitative with descriptive method. The population of this study were all 1st semester students of various majors, totaling 280 people. Samples were taken from 25 percent of the total population or 70 people. The sampling technique used is random sampling. The results of the study describe learning motivation, namely some students have moderate learning motivation and some students have low learning motivation. The low motivation to learn is caused by several factors, including the unsupported media used, unstable internet connection and lack of internet quota for students.